Effectiveness of Early Breastfeeding Initiation (IMD) as an Effort to Preventive Hypothermia in Neonatal: A Literature Study - Mocafiani Sinar Rizki; Sri Lestari Dwi Astuti; Yuyun Setyorini (Interest : Jurnal Ilmu Kesehatan, 2023)
Background: Hypothermia is a leading cause of morbidity and mortality in neonates, contributing to complications such as hypoglycemia, metabolic acidosis, hypoxia, growth disturbances, bleeding, shock, and apnea. One effective prevention method is Early Initiation of Breastfeeding (IMD). This study analyzes the effectiveness of IMD in preventing hypothermia in neonates.  Methods: This literature review used the PICO (Population, Intervention, Comparison, Outcome) approach. Eleven journals from Elsevier, Google Scholar, ResearchGate, PubMed, and Wiley Online Library, published between 2019 and 2023, were reviewed.  Results: The analysis showed that IMD was effective in increasing neonatal body temperature with an average increase of 0.55°C. All journals reviewed concluded that IMD plays a significant role in maintaining the stability of infant body temperature and preventing hypothermia with a p value <0.05.  Conclusion: IMD is effective in preventing hypothermia, enhancing breast milk production, promoting bonding between mother and baby, and strengthening the baby’s immune system. IMD should be initiated as soon as possible after birth, with a minimum duration of 60 minutes, to prevent hypothermia.